Micro-shear bond strength of bioactive cement to translucent zirconia after thermocycyling: a comparative in-vitro study - ElGendy, Menna Ahmed; Mosleh, Ihab; Zaghloul, Hanaa (Brazilian Dental Science, 2020)
Objective: the purpose of the study was to evaluate the micro-shear bond strength of different cements to translucent zirconia before and after thermocycling aging. Material and methods: Twelve translucent zirconia ceramic discs were used in the study. Specimens were sandblasted using 50 ??m aluminum oxide (Al2O3) particles. The specimens were divided into three groups (n = 4) according to the cement type: Panavia resin cement (control group), resin modified glass ionomer (RMGI), and Activa bioactive cement. Each group was further sub-divided into two equal subgroups (n = 2) according to whether the specimens were subjected to thermocycling or not. Thermocycling was performed in distilled water at 5000 cycles between 5 oC - 55 oC. The micro-shear bond strength test (?SBS) was measured using universal testing machine. Kruskal-Wallis test was used to compare between the three cements. Dunn’s test was used for pair-wise comparisons when Kruskal-Wallis test is significant. Mann-Whitney U test was used to compare between micro-shear bond strength before and after thermocycling P ? 0.05. Results: In non-aged subgroups, there was no significant difference between Panavia and Activa; both showed significantly the highest mean ?SBS values (22.9 MPa, 31.3 MPa respectively). While, RMGI showed the lowest ?SBS values (4.7 MPa). In thermocycled subgroups, Panavia showed significantly the highest mean ?SBS values (32.2 MPa). There was no significant difference between RMGI and Activa; both showed the lowest significant mean ?SBS values (3.2 MPa and 8.7 MPa respectively). Conclusions: RMGI and Activa couldn’t be considered long-term reliable materials for cementing zirconia. However, Panavia provided the most durable bond to zirconia. KEYWORDS Bioactive cement; Micro-shear bond strength; Resin cement; Translucent zirconia.